Technology, Trade and Factor Mobility - Douglas D. Purvis (Queen's University, Department of Economics, 1971)
The well-known factor price equalization theorem is often invoked to provide trade theorists with justification for the conventional assumption of complete international immobility of factors of production. If conditions of the theorem are satisfied, and free trade does in fact give rise to the equalization of factor returns, then it is inconsequential in which country production takes place. Mundell's original analysis then brings us full circle to the "commodity price equalization theorem". If the conditions of the factor price equalization theorem are met, but a tariff on trade is imposed, then factor mobility can replace trade in establishing productive efficiency. Recent work by Jones and Kemp have analysed further the implications of introducing factor mobility and in particular capital mobility into the analysis of international trade. However, these have concentrated on generating optimum tariff and tax( on capital services) formulae for the individual country trying to maximize its own welfare. The present paper is more in the tradition of the Mundell analysis in that we are more concerned with world efficiency in production–that is, in maximizing potential world welfare.
Keywords: 330